Mechanisms Underlying Influence of Bioelectricity in Development - George, Laura Faith; Bates, Emily Anne (Frontiers in Cell and Developmental Biology, 2022)
To execute the intricate process of development, cells coordinate across tissues and organs to determine where each cell divides and differentiates. This coordination requires complex communication between cells. Growing evidence suggests that bioelectrical signals controlled via ion channels contribute to cell communication during development. Ion channels collectively regulate the transmembrane potential of cells, and their function plays a conserved role in the development of organisms from flies to humans. Spontaneous calcium oscillations can be found in nearly every cell type and tissue, and disruption of these oscillations leads to defects in development. However, the mechanism by which bioelectricity regulates development is still unclear. Ion channels play essential roles in the processes of cell death, proliferation, migration, and in each of the major canonical developmental signaling pathways. Here we review the evidence for the importance of bioelectricity in development and explore the potential mechanisms by which ion channels may act in developmental pathways.